2020
DOI: 10.1542/peds.2019-4113
|View full text |Cite
|
Sign up to set email alerts
|

Race, Postoperative Complications, and Death in Apparently Healthy Children

Abstract: Drs Nafiu contributed to the idea conception and critical review of literature, drafted the initial manuscript, and reviewed and revised the manuscript; Dr Mpody contributed to the study design, data curation, and analyses and reviewed and revised the manuscript; Drs Kim and Uffman contributed to the idea conception and interpretation of the data and critically reviewed and revised the manuscript; Dr Tobias contributed to the idea conception, oversaw the acquisition and analyses of the data as well as the revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
66
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 27 publications
6
66
2
Order By: Relevance
“…6 One study exhibited an increased rate of postoperative mortality among Black children among other composite complications, even when controlled for comorbidity. 35 These findings further signify the importance of examining the more complex social determinants of health in the assessment of health disparities with the intention to allocate resources to achieve health equity.…”
Section: Health Equity In Pediatric Anesthesiamentioning
confidence: 91%
“…6 One study exhibited an increased rate of postoperative mortality among Black children among other composite complications, even when controlled for comorbidity. 35 These findings further signify the importance of examining the more complex social determinants of health in the assessment of health disparities with the intention to allocate resources to achieve health equity.…”
Section: Health Equity In Pediatric Anesthesiamentioning
confidence: 91%
“…Cultural differences, language problems, and religious beliefs can undoubtedly pose a challenge to the clinician in his/her approach to the patients. A recent survey from the U.S. showed that children of African American ethnicity were 3.5 times more likely to die 30 days after surgery, 18% relative greater odds of developing postoperative complications, and 7% relative greater odds of developing serious adverse events compared to white Americans [9]. The apparent racial disparity could not be explained by differences in preoperative physical status, and although the authors do not conclude that racial discrimination is a direct cause, one can speculate about how low social status, different educational level, and religious belief as contributing factors in how healthcare workers interact in the caring of this group of patients.…”
Section: Rights To Non-discriminationmentioning
confidence: 99%
“…1,18 These disparities persist even in apparently healthy children who are expected to develop few complications. 19 Concordant with the disparity in surgical outcomes for Black children is the exponential increase in surgical cost, driven partly by advances in surgical techniques but principally by complications. [20][21][22][23] However, little is known about the excess costs to the health care system related to disparities based on race.…”
mentioning
confidence: 99%
“…This study builds on our previous work demonstrating disparities between Black and white children undergoing surgery, including the use of do-not-resuscitate orders, 30 pain management, 31 and risk of death. 19,32 To identify interventions to address disparities between Black and white children, we decided a priori to focus specifically on the trends in pediatric appendectomy outcomes and the related health care system costs attributable to disparities in postappendectomy complications among Black and white children.…”
mentioning
confidence: 99%